Cladistic analysis of Omalodini Kryzhanovskij (Coleoptera: Histeridae: Histerinae). (27th October 2014) - LEIVAS, FERNANDO W. T.; BICHO, CARLA L.; ALMEIDA, LÚCIA M.
Abstract According to the current Histeridae classification, Omalodini is composed of 100 species described in 12 genera distributed in the Neotropical, Afrotropical, Afrotemperate and Oriental regions: Asolenus Lewis; Atribalus Bickhardt; Blypotehus Vienna, Ebonius Lewis; Lewisister Bickhardt; Notolister Lewis; Omalodes Erichson, divided in Omalodes (Omalodes), O. (Diplogrammicus) Lewis and O. (Cornillus) Lewis; Perfidolenus Vienna; Rhypochares Marseul; Scapomegas Lacordaire; Sphyracus Marseul; Theropatina Mazur. Our aims were to test the monophyly of Omalodini, using cladistic analysis, and propose a hypothesis of the phylogeny of the tribe. The matrix was composed of 49 terminal taxa (34 from the ingroup and 15 from the outgroup) and 131 characters of the adult morphology. The data were analysed under equal weights and implied weights. In both analyses, Omalodini represents a polyphyletic group and the trees obtained from equal weights analysis (two most parsimonious trees) were chosen in order to recover the tribe's monophyly. We recognize three lineages in Omalodini: Ebonius, undescribed genus and Omalodes, being supported by six transformations (Ebonius + (undescribed genus + Omalodes)). The sister group of Omalodini was defined as a clade composed of Histerini, Platysomatini and Hololeptini. The subgenera of Omalodes were not resolved consistently under different implied weight analyses. It is necessary to emphasize that Omalodes (Omalodes) comprises the largest group of Omalodini and requires an analysis with better sampling for more precise resolution of the internal phylogeny of the genus. The groups excluded a posteriori from Omalodini, Theropatina, Asolenus, Atribalus, Blypotehus, Lewisister, Notolister, Perfidolenus, Rhypochares, Sphyracus and Scapomegas, could not be allocated to any of the existing tribes of Histerinae.